Dampak Program Bank Sampah terhadap Tingkat Pendapatan Nasabah Bank Sampah - Risa Valentine; Muhammad Yasin (Jurnal Riset dan Inovasi Manajemen, 2023)
One of the major breakthroughs in waste management in Indonesia is the waste bank program. Through this program, it is formed in people's minds that waste is something that is useless and is simply thrown away, converted into something that also has value and price. Through the waste bank, people can save waste, which can then generate money within a certain period of time. This research uses descriptive research methods with quantitative analysis. This study aims to find out how the impact of the waste bank program on the socio-economic community in Sememi Village, Benowo District, Surabaya City. Impact is defined as an influence that brings both positive and negative consequences. Based on the results of data analysis, it was concluded that there was a positive impact on the socio-economic life of the people in Sememi Village, Benowo District after the construction of the Garbage Bank. This is indicated by an increase in people's income, although it is small, it provides significant benefits for the community. Not only income has increased, but health and better social interaction among people, most importantly, a cleaner environment has also increased from time to time.